1978
DOI: 10.1128/jb.133.1.372-386.1978
|View full text |Cite
|
Sign up to set email alerts
|

Structural arrangement of polymers within the wall of Streptococcus faecalis

Abstract: The structure of the cell wall of Streptococcus faecalis was studied in thin sections and freeze fractures of whole cells and partially purified wall fractions. Also, the structures of wall preparations treated with hot trichloroacetic acid to remove non-peptidoglycan wall polymers were compared with wall preparations that possess a full complement of accessory polymers. The appearance of the wall varied with the degree of hydration of preparations and physical removal of the cell membrane from the wall before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The teichuronic polymer on the wall surface, our results (and 2.0 mg ml-'. those of others using different walls [14,18,38] J. BACTERIOL.…”
Section: Fig 14mentioning
confidence: 92%
“…The teichuronic polymer on the wall surface, our results (and 2.0 mg ml-'. those of others using different walls [14,18,38] J. BACTERIOL.…”
Section: Fig 14mentioning
confidence: 92%
“…Shockman et al (7,38) used SDS and the closely related and more soluble decyl sulfate to inhibit autolysins of streptococcal cell walls. Tsien et al (40) similarly employed decyl sulfate to treat cell wall fractions destined for morphological study. Boothby et al (5) found that the extraction of Streptococcusfaecalis ATCC 9790 with 2% decyl sulfate after an initial extraction with hot 10% trichloroacetic acid failed to improve the removal of protein from the preparation.…”
mentioning
confidence: 99%
“…In the past, we have used the freeze-etch technique to assess the relative solids or water content or both of bacterial structures (2,11). For example, when exponential-phase cells of Streptococcus faecalis and other bacteria are cross-fractured, the nucleoid is invisible; no portions of the cytoplasm undergo preferential sublimation to reveal the fibrous character of the chromosomal material (2).…”
mentioning
confidence: 99%